(untitled) (Quinto Sol, 2020)
In the second decade of the 21st century, a highly contagious pandemic crosses the global scene carrying not only its burden of mortality and morbidity, but also an intense campaign to regulate social behaviors through the sanitization of habits and behaviors, with the imposition of a new biopower. In a highly communicated (and at the same time, isolated) post-industrial society, this virus allows a new reflection on ethics and individual morals, responsible for the advance or restriction of the epidemic. Never before has a disease of this magnitude and speed been "constructed" in real time, despite not being the most lethal epidemic onset to affect human beings. Neither the Black Death in fourteenth century Italy, or smallpox in the America of "discovery" (and destruction) had such a high media impact, since they were installed on societies where illiteracy and little information was the norm. Neither did yellow fever or cholera in the smelly cities on either side of the Atlantic and Pacific nineteenth century, and even the millions of deaths from the flu epidemic that surpassed those of the First World War, had the attention of the majority, nor from governments and international entities, as the new coronavirus has it today, or COVID-19